The use of influential power in ocean governance - Haas, Bianca; Jaeckel, Aline; Pouponneau, Angelique; Sacedon, Randa; Singh, Gerald G.; Cisneros-Montemayor, Andrés M. (Frontiers in Marine Science, 2023)
Ensuring inclusivity, especially the meaningful participation of diverse actors, is a key component of good governance. However, existing ocean governance frameworks have not yet achieved an equitable and fair playing field and are indeed often characterized by inequitable practices. In this perspective piece, we argue that one of the reasons for this lack of inclusion are the existing power frameworks and ways in which power is exercised within fora nominally intended to foster inclusion and cooperation. By focusing on four case studies of basic ocean governance processes, we explore how influential and interactive power is exercised in intergovernmental meetings, international conferences, and regional negotiations. These case studies demonstrate how specific exercises of power that undermine procedural inclusivity influence decision-making and the setting of agendas, and exclude important voices from ocean governance fora. This perspective piece contributes to the existing literature on power by highlighting how power is exercised within fundamental aspects of ocean governance. This paper merely scratches the surface, and more actions and research are needed to uncover and, more importantly, reverse deeply-rooted and self-perpetuating power structures in ocean governance.